Sea Level Fluctuations - Dolgikh, Grigory Ivanovich (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This thematic issue presents 11 scientific articles that are extremely useful for understanding the processes and phenomena of the interacting geospheres of the Earth. These processes have an important impact on the biosphere and many human activities. The results of scientific research presented in this book are fully united by the common theme "investigation of the fundamental foundations of the emergence, development, transformation, and interaction of hydroacoustic, hydrophysical and geophysical fields in the World Ocean." The book is recommended to a wide range of readers, as well as to specialists in the field of hydroacoustics, oceanology, and geophysics.